2020
DOI: 10.3390/inorganics9010001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Functional Groups and Missing Linkers on the Adsorption Capacity of Aromatic Hydrocarbons in UiO-66 Thin Films

Abstract: The adsorption of benzene, toluene, ethylbenzene, and xylene isomers, also known as BTEX, from the gas phase into porous thin films of the metal–organic framework UiO-66-X, where X = H, NH2, and NO2, was measured to quantify adsorption capacity. The thin films were grown by a vapor-conversion method onto Au-coated quartz microbalance crystals. The MOF thin films were characterized by IR and Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy and scanning electron microscopy. The thin films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…At this point, it is interested to highlight that, in spite of the proper crystallinity, functionalization gives rise to significant changes in the I (111) / I (002) ratio. Previous results described in the literature have shown that these variations are a clear indication of the presence of structural defects in UiO-66 samples. , More specifically, these changes are consistent with the presence of missing linker defects (the 002 reflection is systematically more intense when linkers are missing). The I (111) / I (002) ratio changes from 2.8 in the nonfunctionalized UiO-66 down to 1.4 for UiO-66-NH 2 and 1.2 for UiO-66-NO 2 (see the inset in Figure ).…”
Section: Results and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…At this point, it is interested to highlight that, in spite of the proper crystallinity, functionalization gives rise to significant changes in the I (111) / I (002) ratio. Previous results described in the literature have shown that these variations are a clear indication of the presence of structural defects in UiO-66 samples. , More specifically, these changes are consistent with the presence of missing linker defects (the 002 reflection is systematically more intense when linkers are missing). The I (111) / I (002) ratio changes from 2.8 in the nonfunctionalized UiO-66 down to 1.4 for UiO-66-NH 2 and 1.2 for UiO-66-NO 2 (see the inset in Figure ).…”
Section: Results and Discussionsupporting
confidence: 79%
“…At this point, it is interesting to highlight that whereas the nonfunctionalized UiO-66 loses more than 60% of its weight at 800 °C, functionalized derivatives lose less than 55% of the original weight. The higher residual weight at 800 °C in the functionalized MOFs could be another indication of the structural defects (missing linkers) anticipated by the XRD measurements. ,, From the TG analysis, a higher number of defects can be inferred for samples UiO-66-NH 2 (after removing humidity), although UiO-66-NO 2 has a larger structural instability.…”
Section: Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The adsorption capacities is larger for the C 8 isomers within Ni-MOF-74 and Co-MOF-74 thin films than for UiO-66 thin films. 64 Presumably, this is due to the larger pores and presence of channels lined by open metal coordination sites in the MOF-74 framework that promotes Lewis acid−base πcomplexation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the peak increase at 1613 cm À1 can be indexed to the C-C bond stretching mode of the linker aromatic ring. 80 Several other peaks also experience slight enhancements, indicating the appearance of functional groups belonging to glucose. The peaks at 200-500 cm À1 represent the main skeletal vibrational motions of glucose, which correspond to d (C-C-C), d (C-C-O), and s (C-C).…”
Section: Signal Amplicationmentioning
confidence: 99%